Wyo. Comp. Laws (1876) ch. 35, § 127, as codified in Wyo. Rev. Stat., Crimes (1887), Having possession of offensive weapons, § 1027 - (:unkn) unknown (General Publisher, 1876)
Prohibited the carrying of a pistol, knife, dirk, bludgeon, or other offensive weapon with the intent to assault a person. Punishable by fine up to $500 or imprisonment up to 6 months.
--
Keywords: CARRY - INTENT TO COMMIT CRIME